The relationship between fatigue and play activities of children with acute lymphoblastic leukemia receiving chemotherapy - Arini, Tri; Widjajanto, Pudjo Hagung; Haryanti, Fitri (International Journal of Research in Medical Sciences, 2017)
Background: Children with cancer tend to have various complaints during chemotherapy. Fatigue is one of the most frequent and severe symptoms experienced by paediatric oncology patients during treatment. This study performed to analyse the correlation of fatigue to play activity in children with acute lymphoblastic leukemia (ALL) who undergo chemotherapy. Methods: Quantitative desaign, correlation study using cross-sectional approach to 69 children aged within age of 2—12 years treated at Dr. Sardjito General Hospital, Yogyakarta with ALL. Data were collected using PedsQL Multidimensional Fatigue Scale instrument to quantify children’s fatigue through self-report and parent’s report. Play Performance Scale for Children was used to measure children’s play activity. Data were analyzed statistically by Spearman’s rho and Kendall’s tau nonparametric correlation tests. Results: The total fatigue score based on children’s self-reports and parent’s reports averaged between 50 and 75. This indicates that children sometimes to almost never experience fatigue. Total score of fatigue –child self-report (70.50) was lower compared with parent’s report (70.93). Children’s play activity reported by parents was scored at 70.72. There was a significant positive correlation between children’s self-reported total fatigue score and play activity with medium correlation strength (r=0.40, p=0.02). The correlation between children’s parent-reported total fatigue score and play activity was also significantly positive with a weak correlation strength (r=0.27, p=0.003). Conclusions: There is a positive correlation between children’s self-reported and parent-reported fatigue with play activity in children with ALL. This suggests that as the child experience less fatigue, their play activity will increase to near-normal.